Multiple-dose tolerability, pharmacokinetics, and pharmacodynamics of ponesimod, an S1P1 receptor modulator: favorable impact of dose up-titration - Brossard, P; Scherz, M; Halabi, A; Maatouk, H; Krause, A; Dingemanse, J (Journal of clinical pharmacology, 2014)
This multiple-ascending-dose study investigated the safety, tolerability, pharmacokinetics, and pharmacodynamics of ponesimod, an S1P1 receptor modulator and a potential new treatment for autoimmune diseases. In part A, 10 healthy male and female subjects received once daily oral doses of ponesimod (5, 10, or 20 mg) or placebo for 7 days. Sinus bradycardia and, in some subjects, atrioventricular (AV) block occurred primarily on the first day of dosing, as desensitization developed to ponesimod-induced heart rate (HR) reduction and PR-prolongation. This elicited the design of an up-titration schedule in 17 subjects to a dose of 40 mg in part B. The up-titration regimen reduced HR and PQ/PR effects. Reported adverse events were mainly related to the cardiac and respiratory systems. Respiratory effects increased with higher doses. Ponesimod multiple-dose pharmacokinetics were slightly more than dose-proportional and characterized by a time to maximum concentration and an elimination half-life varying from 2.5 to 4.0 hours and 30.9 to 33.5 hours, respectively, and an accumulation of about 2.3-fold. Ponesimod caused a dose-dependent sustained decrease in total lymphocyte count, reversible within 7 days of discontinuation. A pharmacokinetic-pharmacodynamic model enabled comparing day 1 and steady-state conditions. These results warrant further investigation of ponesimod in patients.